2019
DOI: 10.1002/ana.25524
|View full text |Cite
|
Sign up to set email alerts
|

PDXK mutations cause polyneuropathy responsive to pyridoxal 5′‐phosphate supplementation

Abstract: Objective To identify disease‐causing variants in autosomal recessive axonal polyneuropathy with optic atrophy and provide targeted replacement therapy. Methods We performed genome‐wide sequencing, homozygosity mapping, and segregation analysis for novel disease‐causing gene discovery. We used circular dichroism to show secondary structure changes and isothermal titration calorimetry to investigate the impact of variants on adenosine triphosphate (ATP) binding. Pathogenicity was further supported by enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 68 publications
0
48
0
1
Order By: Relevance
“…Finally, a PLP (pyr-idoxal 5 0 -phosphate)-responsive primary axonal peripheral neuropathy and optic atrophy have recently been associated with recessive mutations in PDXK (MIM: 179020), encoding a gene involved in converting pyridoxal to the active form of B6, PLP. 26 Given the fact that some children with IGDs have pyridoxine-responsive seizures, this is interesting because alkaline phosphatase also converts PLP to pyridoxal, and this process is essential for B6 to reach the central nervous system (CNS). The mechanism at play in the neuropathy seen in the individuals described here would benefit from model organism studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a PLP (pyr-idoxal 5 0 -phosphate)-responsive primary axonal peripheral neuropathy and optic atrophy have recently been associated with recessive mutations in PDXK (MIM: 179020), encoding a gene involved in converting pyridoxal to the active form of B6, PLP. 26 Given the fact that some children with IGDs have pyridoxine-responsive seizures, this is interesting because alkaline phosphatase also converts PLP to pyridoxal, and this process is essential for B6 to reach the central nervous system (CNS). The mechanism at play in the neuropathy seen in the individuals described here would benefit from model organism studies.…”
Section: Discussionmentioning
confidence: 99%
“…This collection consists of 109 different co-expression networks ( Supplementary Table 1 ) that belong to four different network groups: (1) the Religious Orders Study and Memory and Aging Project (ROSMAP) ( Bennett et al, 2012a , b ; De Jager et al, 2018 ) composed of four co-expression networks derived from post-mortem human frontal cortex originating from control individuals, as well as those with cognitive impairment and Alzheimer’s disease; (2) The Genotype-Tissue Expression project (GTEx) V6 and V7 ( The GTEx Consortium, 2015 ) composed of two suites of GCNs on 47 and 51 post-mortem control human tissue samples, respectively; (3) United Kingdom Brain Expression Consortium (UKBEC) ( Forabosco et al, 2013 ; UK Brain Expression Consortium, et al, 2014 ) composed of 10 microarray-based gene expression profiling networks derived from post-mortem control human brain tissue; (4) North America Brain Expression Consortium (NABEC) ( Dillman et al, 2017 ), composed of one gene co-expression network derived from post-mortem control human frontal cortex. Through CoExp, we and others have used these models to provide annotations for genes and gene sets in a variety of papers ( Chelban et al, 2017 , 2019 ; Salpietro et al, 2017 , 2018 ; Efthymiou et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the reasons for prior noninclusion of detected genes in the NMD‐panel to uncover the most frequent reasons for missed panel diagnosis. Our analysis showed that 50% (5/10) of genes were only recently identified as associated with their respective phenotypes, with first reports in the past three years: AGTPBP1 (AR childhood‐onset neurodegeneration with cerebellar atrophy; MIM# 618276; Shashi et al, 2018), ADPRS (AR stress‐induced childhood‐onset neurodegeneration with variable ataxia and seizures; MIM# 618170) (Ghosh et al, 2018), FDXR (AR optic atrophy‐ataxia‐peripheral neuropathy‐global developmental delay syndrome; ORPHA:543470; Peng et al, 2017), PDXK (AR hereditary motor and sensory neuropathy type VIC with optic atrophy; MIM# 618511; Chelban et al, 2019), VPS13D (AR spinocerebellar ataxia 4; MIM# 607317; Gauthier et al, 2018; Seong et al, 2018). The other half was not included due to phenotypic discordance: ARSA (AR metachromatic leukodystrophy; MIM# 250100) was not included because of its characteristic cranial MRI abnormalities usually leading to single‐gene testing (van Rappard et al, 2015), DNM1L (AD/AR encephalopathy due to defective mitochondrial and peroxisomal fission 1; MIM# 614388), ECHS1 (AR mitochondrial short‐chain enoyl‐CoA hydratase‐1 deficiency; MIM# 616277), and SEPSECS (AR pontocerebellar hypoplasia type 2D; MIM# 613811) were not included because of clinical presentation where pure NMD features are not typically most prominent.…”
Section: Resultsmentioning
confidence: 99%